A High Strength Self‐Healable Antibacterial and Anti‐Inflammatory Supramolecular Polymer Hydrogel. Issue 9 (8th March 2017) - Wang, Hongbo; Zhu, Hui; Fu, Weigui; Zhang, Yinyu; Xu, Bing; Gao, Fei; Cao, Zhiqiang; Liu, Wenguang
Abstract : A high strength supramolecular polymer hydrogel with multifunctional performances is prepared by copolymerizing N‐arolyoyl glycinamide (NAGA, hydrogen bonding monomer) with 1‐vinyl‐1, 2, 4‐triazole (VTZ). Triazole residues endow the obtained hydrogels with antibacterial and anti‐inflammatory activities, and dynamic hydrogen bonding contributes to an excellent self‐healability and thermoprocessability. This work offers a simplified way to fabricate antibacterial biohydrogels for treating degenerated load‐bearing tissues. Abstract : There is a significant cost to mitigate the infection and inflammation associated with the implantable medical devices. The development of effective antibacterial and anti‐inflammatory biomaterials with novel mechanism of action has become an urgent task. In this study, a supramolecular polymer hydrogel is synthesized by the copolymerization of N ‐acryloyl glycinamide and 1‐vinyl‐1, 2, 4‐triazole in the absence of any chemical crosslinker. The hydrogel network is crosslinked through the hydrogen bond interactions between dual amide motifs in the side chain of N ‐acryloyl glycinamide. The prepared hydrogels demonstrate excellent mechanical properties—high tensile strength (≈1.2 MPa), large stretchability (≈1300%), and outstanding compressive strength (≈11 MPa) at swelling equilibrium state. A simulation study elaborates the changes of hydrogen bond interactions when 1‐vinyl‐1, 2, 4‐triazole is introduced into the gel network. It is demonstrated that the introduction of 1‐vinyl‐1, 2, 4‐triazole endowes the supramolecular hydrogels with self‐repairability, thermoplasticity, and reprocessability over a lower temperature range for 3D printing of different shapes and patterns under simplified thermomelting extrusion condition. In addition, these hydrogels exhibit antimicrobial and anti‐inflammatory activities, and in vitro cytotoxicity assay and histological staining following in vivo implantation confirm the biocompatibility of the hydrogel. These hydrogels with integrated multifunctions hold promising potential as an injectable biomaterial for treating degenerated soft supporting tissues.